Never outside the labour market, but always outsiders: female migrant workers in Greece - Tastsoglou, Evangelia; Hadjicostandi, Joanna (The Greek Review of Social Research, 2003)
This article focuses on migrant women’s diverse experiences in the Greek labour market. Since the early 1980s all four Southern European countries of the EU, Spain, Portugal, Greece and Italy, have been transformed from emigration into immigration countries. The new immigrants, mostly undocumented and illegal, join the informal labour market under highly exploitative conditions. Starting from migrant women’s own perspectives, we analyze their experiences (1) in the framework of the unfolding ≪Mediterranean immigration model≫ (2) in the midst of increasing ≪South≫ – ≪North≫ migrations and increasing migratory flows to Greece in particular; (3) in the context of the legal and policy framework for migrants in Greece; and (4) in the framework of women’s citizenship in society. Our qualitative study of immigrant women in Greece fleshes out the general trends of women's participation in informal labour markets, documents the multi-layered nature of their economic and social exclusion, and highlights the intersecting racialization and sexist practices shaping their experiences